Bawk & roll - Sauer, Tammi (Chicken dance, 2012)
"Dancing chickens Marge and Lola have flown the coop to shake, wattle, and roll on tour with superstar singer Elvis Poutry. Will the hens bawk at fame and lay a rotten egg in concert? Or will they rise to the top of the pecking order and give the crowds something to crow about?"--